Self Efficacy Scale For People With Drug Abuse Disorders - Agus Supriyanto; Nurlita Hendiani (JKI (Jurnal Konseling Indonesia), 2018)
Intent to influence the process of recovery and relapse prevention for people with Substance Abuse Disorders (GPZ), which is being rehabilitated. The purpose of the study was to find the dimension of self-efficacy people with GPZ to recover from drug addiction, as well as valid and reliable statement items on self-efficacy scale instruments. This study used a mixed methods approach with the transformative sequential design. Instrument research through documentation studies, interviews, and surveys with N = 217. Qualitative descriptive analysis through the study of journal and book, focus group discussion for the determination of the statement items. Quantitative descriptive analysis to know the validity and reliability of the instrument. The findings reveal indicators of self-efficacy scales to recover from addiction through three dimensions, ie (1) level dimension, (2) general dimension, and (3) strength dimension. The self-efficacy scale has 32 valid statements with a coefficient of Corrected Item-Total Correlation ≥ 0148 and has a reliability coefficient of 0.862 with a high category. Self-efficacy scales are useful identifying confidence levels for people's with GPZ during rehabilitation programs and counseling development.